Cross-sectional study of seropositivity, lung lesions and associated risk factors of the main pathogens of Porcine Respiratory Diseases Complex (PRDC) in Goiás, Brazil - Galdeano, José Vanderlei Burim [UNESP]; Baraldi, Thaís Gasparini [UNESP]; Ferraz, Maria Eugênia Silveira [UNESP]; De Souza Almeida, Henrique Meiroz [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Costa, Willian Marcos Teixeira; Montassier, Hélio José [UNESP]; Mathias, Luis Antonio [UNESP]; De Oliveira, Luís Guilherme [UNESP] (Springer Nature, 2019)
Background: The objective of the study was to evaluate the occurrence and severity of Porcine Respiratory Diseases Complex (PRDC) pathogens in the Goiás State, Brazil. Were assessed the serological antibodies occurrency of Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae and swine influenza virus (SIV), as well as the evaluation of pulmonary Mycoplasma-like lung lesions, pleuritis, histopathological lesions and diseases occurrence associated with risk factors, such as management, housing and productive indexes. We conveniently selected 2536 animals for serology testing, and 900 lungs at slaughtering of animals from 30 multisite herds in Goiás State, Brazil. Results: For M. hyopneumoniae, all herds presented seropositive animals at some stage of production. Even though most herds (29/30) vaccinated against this pathogen, 90.0% (27/30) of the herds presented at least 50.0% of seropositive animals in finishing and slaughter. Overall, antibodies against A. pleuropneumoniae were present in lower occurrence, varying from 22.4% of the animals in the nursery phase to 1.3% of the animals at slaughter. Conversely, SIV circulated in most herds, with 29 seropositive herds without vaccination. The occurrence of anti-SIV antibodies was higher at slaughter (74.5% of the animals) than nursery (41.8% of the animals), and at slaughter, 23 herds (76.7%) presented at least 50.0% of seropositive animals. All herds presented animals with pulmonary Mycoplasma-like lung lesions, and of the 900 lungs evaluated in the slaughterhouse, 665 (73.9%) presented an average Mycoplasma-like lung lesions of 7.3%. Evaluations of the pneumonia index (PI) showed that 73.3% of the herds were strongly affected by a pathology that manifested itself in different presentation forms. Microscopically, there was a predominance of bronchopneumonia lesions (74.6% of affected lungs), with a high occurrence of the chronic form (57.1%), and there was a moderate to marked proliferation of bronchial associated lymphoid tissue (BALT) in 64.1% of the affected lungs. Pleuritis were observed in 13.5% of the animals. Conclusion: Serological tests evidenced that antibodies against App and SIV were present in the Goiás State herds, and high occurrence of M. hyopneumoniae antibodies in finishing phases and slaughter may be influenced by pathogen circulation in vaccinated herds, leading to respiratory lesions at slaughter. Additionally, swine influenza virus was broadly disseminated in technified herds in Goiás State.
Keywords: Mycoplasma-like lung lesion; Pleuritis; Pneumonia; PRDC; Serology; Swine